Afri-Can Forum 2. Issue 2 (July 2016) - Mukudu, Hillary; Martinson, Neil; Sartorius, Benn; Coetzee, Jenny; Dietrich, Janan; Mokgatswana, Kgaugelo; Jewkes, Rachel; Gray, Glenda; Dugas, Marylène; Béhanzin, Luc; Guédou, Fernand; Gagnon, Marie-Pierre; et al.
Table of contents A1 Introduction to the 2nd synchronicity forum of GHRI/CHVI-funded Canadian and African HIV prevention and vaccine teams O1 Voluntary medical male circumcision for prevention of heterosexual transmission of HIV in adult males in Soweto: What do indicators and incidence rate show? Hillary Mukudu, Neil Martinson, Benn Sartorius O2 Developing a peer-led community mobilization program for sex workers in Soweto: HIV risk and demographics Jenny Coetzee, Janan Dietrich, Kgaugelo Mokgatswana, Rachel Jewkes, Glenda E. Gray O3 Salient beliefs about adherence: A qualitative survey conducted as part of the demonstration study on "treatment as prevention" (TasP) and "pre-exposure prophylaxis" (PrEP) among female sex workers (FSWS) in Cotonou, Benin Marylène Dugas, Luc Béhanzin, Fernand A. Guédou, Marie-Pierre Gagnon, Michel Alary O4 Relative perception of risk as a driver of unsafe sexual practices among key populations: Cases of fisherfolk and women and their partners involved in multiple sexual partnerships in Uganda Rwamahe Rutakumwa, Martin Mbonye, Thadeus Kiwanuka, Sarah Nakamanya, Richard Muhumuza, Winfred Nalukenge, Janet Seeley O5 Exploring the acceptability of new biomedical HIV prevention technologies among MSM, adolescents and heterosexual adults in South Africa Millicent Atujuna, Melissa Wallace, Ben Brown, Linda Gail Bekker, Peter A. Newman O6 HIV-susceptible target cells in foreskins after voluntary medical male circumcision in South Africa Rushil Harryparsad, Abraham J. Olivier, Heather B. Jaspan, Douglas Wilson, Janan Dietrich, Neil Martinson, Hillary Mukudu, Nonhlanhla Mkhize, Lynn Morris, Gianguido Cianci, Minh Dinh, Thomas Hope, Jo-Ann S. Passmore, Clive M. Gray O7 HIV-1 proteins activate innate immune responses via TLR2 heterodimers Bethany M. Henrick, Xiao-Dan Yao, Kenneth L. Rosenthal, the INFANT Study Team O8 Characterization of an innate factor in human milk and mechanisms of action against HIV-1 Bethany M. Henrick, Xiao-Dan Yao, Anna G. Drannik, Alash'le Abimiku, Kenneth L. Rosenthal, the INFANT Study Team O9 Secretor status and susceptibility to HIV infections among female sex workers in Nairobi, Kenya Nadia Chanzu, Walter Mwanda, Julius Oyugi, Omu Anzala O10 Natural Killer cell recall responsiveness to Gag-HIV-1 peptides of HIV-1 exposed but uninfected subjects are associated with peripheral CXCR6+ NK cell subsets Moustapha Mbow, Sabelle Jallow, Moussa Thiam, Alberta Davis, Assane Diouf, Cheikh T. Ndour, Moussa Seydi, Tandakha N. Dieye, Souleymane Mboup, Martin Goodier, Eleanor Rilley, Assan Jaye O11 Profiles of resistance: Local innate mucosal immunity to HIV-1 in commercial sex workers Xiao-Dan Yao, RW. Omange, Bethany M. Henrick, Richard T. Lester, Joshua Kimani, T. Blake Ball, Francis A. Plummer, Kenneth L. Rosenthal O12 Early antiretroviral therapy and pre-exposure prophylaxis for HIV prevention among female sex workers in Cotonou, Benin: A demonstration project Luc Béhanzin, Fernand A. Guédou, Nassirou Geraldo, Ella Goma Mastétsé, Jerôme Charles Sossa, Marcel Djimon Zannou, Michel Alary O13 Building capacity for HIV prevention trials: Preliminary data from a Nigerian cohort of HIV exposed sero-negatives (HESN) Sophia Osawe, Evaezi Okpokoro, Felicia Okolo, Stephen Umaru, Rebecca Abimiku, Sam Audu, Pam Datong, Alash'le Abimiku O14 Equipping healthcare professionals with skills required for the conduct of clinical trials in an effort to build capacity. Lessons learned Jacquelyn Nyange, Joyce Olenja, Gaudensia Mutua, Walter Jaoko, Gloria Omosa-Manyonyi, Bashir Farah, Maureen Khaniri, Omu Anzala O15 Educational technology to support active learning for HIV researchers and planners Anne Cockcroft, Kendra Tonkin, Indu Girish, Puna Mhati, Ashley Cunningham, Neil Andersson O16 From Lake Kivu (Rwanda) and Lake Malawi (Tanzania) to the shores of Lake Victoria (Uganda): Strengthening laboratory capacity through Good Clinical Laboratory Practice training Bashir Farah, Jackton Indangasi, Walter Jaoko, Gaudensia Mutua, Maureen Khaniri, Jacquelyn Nyange, Omu Anzala O17 Rilpivirine and etravirine resistance mutations in HIV-1 subtype C infected patients on a non-nucleoside reverse transcriptase inhibitor-based combination antiretroviral therapy in Botswana Thabo Diphoko, Simani Gaseitsiwe, Victoria Maiswe, Thato Iketleng, Dorcas Maruapula, Keabetswe Bedi, Sikhulile Moyo, Rosemary Musonda, Mark Wainberg, Joseph Makhema, Vladimir Novitsky, Richard Marlink, Max Essex O18 From home-based HIV testing to initiation of treatment: The AIDS Support Organization (TASO) Experience with Home-based HIV Counselling and Testing (HBHCT) among Adolescents in Uganda, 2005-2011 Stephen Okoboi, Livingstone Ssali, Sam Kalibala, Josephine Birungi, Aggrey Egessa, Jonathan Wangisi, Lyavala Joanne Okullu, Celestin Bakanda, Francis Obare41 O19 Feasibility study on using real time medication monitoring among HIV infected and Tuberculosis patients in Kilimanjaro, Tanzania I. Marion Sumari-de Boer, Hadija H. Semvua, Jossy van den Boogaard, Krisanta W. Kiwango, Kennedy M. Ngowi, Pythia T. Nieuwkerk, Rob E. Aarnoutse, Ireen Kiwelu, Eva Muro, Gibson S. Kibiki O20 Deaths still among sero-discordant cohort in Nigeria despite Access to treatment Ruth Datiri, Grace Choji, Sophia Osawe, Evaezi Okpokoro, Felicia Okolo, Stephen Umaru, Rebecca Abimiku, Samuel Audu, Pam Datong, Alash'le Abimiku O21 Therapeutic HIV-1 vaccine trials in Denmark and Guinea-Bissau Fomsgaard A, Karlsson I, Jensen KJ, Jensen SS, Leo-Hansen C, Jespersen S, Da Silva Té D, Rodrigues CM, da Silva ZJ, Janitzek CM, Gerstoft J, Kronborg G, the WAPHIR Group O22 Willingness to participate in a HIV vaccine Trial among HIV exposed sero-negative (HESN) persons in Jos, Nigeria Evaezi Okpokoro, Sophia Osawe, Ruth Daitiri, Grace Choji, Stephen Umaru, Felicia Okolo, Pam Datong, Alash'le Abimiku O23 Clinical research volunteers' perceptions and experiences of screening for enrolment at KAVI-Institute of Clinical Research, Kenya Nyariki Emily, Olenja Joyce, Lorway R. Robert, Anzala Anzala O24 Gut microbiome, HIV-exposure, and vaccine responses in South African infants Katie Viljoen, Jerome Wendoh, Elvis Kidzeru, Ulas Karaoz, Eoin Brodie, Gerrit Botha, Nicola Mulder, Clive Gray, William Cameron, Alain Stintzi, Heather Jaspan, for the INFANT study team O25 Analysis of HIV pol diversity in the concentrated HIV epidemic in Saskatchewan Paul N. Levett, David Alexander, Naveed Gulzar, Prabvir S. Grewal, Art F. Y. Poon, Zabrina Brumme, P. Richard Harrigan, James I. Brooks, Paul A. Sandstrom, Stryker Calvez, Stephen E. Sanche, Jamie K. Scott P1 Evaluating a HIV vaccine research community engagement programme at two HIV prevention research centres in the Western Cape Leslie Swartz, Ashraf Kagee, Anthea Lesch, Zuhayr Kafaar, Anneliese De Wet P2 Validating HIV acquisition risk score using a cohort HIV exposed sero-negative persons in a discordant relationship in Jos, Nigeria, West Africa Evaezi Okpokoro, Sophia Osawe, Ruth Daitiri, Grace Choji, Stephen Umaru, Felicia Okolo, Pam Datong, Alash'le Abimiku P3 Bridging the gap between adults and adolescents and youth adults (AYA) – Employing a youth-centred approach to investigate HIV risk among AYA in Soweto and Durban, South Africa Janan Dietrich, Tricia Smith, Laura Cotton, Stefanie Hornschuh, Martin van der Watt, Cari L. Miller, Glenda Gray, Jenni Smit, Manjeetha Jaggernath, Thumbi Ndung'u, Mark Brockman, Angela Kaida, on behalf of the AYAZAZI study teams P4 Neighbours to sex workers: A key population that has been ignored Maureen Akolo, Joshua Kimani, Prof Larry Gelmon, Michael Chitwa, Justus Osero P5 Young women's access to structural support programmes in a district of Botswana Anne Cockcroft, Nobantu Marokoane, Leagajang Kgakole, Boikhutso Maswabi, Neo Mpofu, Umaira Ansari, Neil Andersson P6 Voices for action from peri-urban Ugandan students, teachers and parents on HIV/STI prevention: Qualitative research results Nakinobe Elizabeth, Miiro George Mukalazi, Zalwango Flavia, Nakiyingi-Miiro Jessica, Kaleebu Potiano P7 Engaging Social Media as an education tool on the fly: The use of Facebook for HIV and Ebola prevention and awareness amongst adolescents in Uganda John Ross Semwanga, Emily Nyanzi, Saidat Namuli Musoke, Elizabeth Nakinobe, George Miiro, Edward Katongole Mbidde, Tom Lutalo, Pontiano Kaleebu P8 Circulating HIV-1 subtypes among sexual minority populations in Zambia Ray Handema, Graham P. Chianzu P9 The Development of HIV Bio-bank resource management to support clinical trial and Intervention research: WAPHIR experience Moussa Thiam, Diabou Diagne-Gueye, Mame K. Ndiaye, Moustapha Mbow, Birahim P. Ndiaye, Ibrahima Traore, Mamadou C. Dia, Gilleh Thomas, Coumba Tour-Kane, Souleymane Mboup, Assan Jaye P10 Capacity building for clinical trials as a novel approach for scaling up HIV prevention research initiatives in East Africa: achievements and challenges Emily Nyanzi, Edward Katongole Mbidde, Pontiano Kaleebu, Juliet Mpendo, Joshua Kimani, Josephine Birungi, Winnie Muyindike, Andrew Kambugu P11 Community and media perspective of research; an advocacy workshop on HIV prevention research Hachizovu Sebastian, Handema Ray, Chaponda Mike, Kabuya Jean Bertin, Mulenga Modest P12 Development of a quantitative HIV-1 and HIV-2 real time PCR (qRT-PCR) viral load assay Moussa Thiam, Omar Janha, Alberta Davis, Alfred Amambua-Ngwa, Davis C. Nwakanma, Souleymane Mboup, Assan Jaye P13 Differential effects of sex in a West African Cohort of HIV-1, HIV-2 and HIV-1/2 dual infected patients: Men are worse off Sanne Jespersen, Bo Langhoff Hønge, Joakim Esbjörnsson, Candida Medina, David Da Silva TÉ, Faustino Gomes Correira, Alex Lund Laursen, Lars Østergaard, Andreas Andersen, Peter Aaby, Christian Erikstrup, Christian Wejse, for the Bissau HIV Cohort study group P14 HIV-infected adolescents in transition from pediatric to adult HIV care in Dakar, Senegal: sample characteristics and immunological and virological profiles Siry Dieye, Moussa Sarr, Haby Sy, Helene D Mbodj, Marianne Ndiaye, Amy Ndiaye, Seydi Moussa, Assan Jaye, Souleymane Mboup100 P15 Molecular characterization of vertically transmitted HIV-1 among children born to HIV-1 seropositive mothers in Northern Tanzania Balthazar M. Nyombi, Elichilia R. Shao, Innocent B. Chilumba, Sikhulile Moyo, Simani Gaseitsiwe, Rosemary Musonda P16 Breast-fed HIV-1 exposed infants play catch up. A preliminary report Pam Datong, Bucky Inyang, Sophia Osawe, Abel Izang, Chundung Cole, Felicia Okolo, Bill Cameron, Kenneth Rosenthal, Clive Gray, Heather Jaspan, Alash'le Abimiku, the INFANT study team P17 The frequency of N348I mutation in patient failing combination antiretroviral treatment In Botswana Boitumelo Seraise, Kerstin Andrea-Marobela, Sikhulile Moyo, Rosemary Musonda, Joseph Makhema, Max Essex, Simani Gaseitsiwe